Respuesta :

snog

Answer:

C

Step-by-step explanation:

You basically multiply the 2 functions together which gives you (2x + 3)(x + 1) = 2x² + 5x + 3

Answer:

The answer is C.

Step-by-step explanation:

Given that f(x) = 2x + 3 and g(x) = x + 1. So you have to multiply both functions together :

[tex]f(x) = 2x + 3 \\ g(x) = x + 1[/tex]

[tex]f(x) \times g(x)[/tex]

[tex] = (2x + 3)(x + 1)[/tex]

[tex] = 2x(x) + 2x(1) + 3(x) + 3(1)[/tex]

[tex] = 2 {x}^{2} + 2x + 3x + 3[/tex]

[tex] = 2 {x}^{2} + 5x + 3[/tex]